How the Sustainable Development Goals risk undermining efforts to address environmental and social issues in the small-scale mining sector. Issue 114 (December 2020) - Hirons, Mark
Highlights: Reviews linkages between the SDGs and ASM and examines prospects for synergies and antagonisms. Engages with 3 key debates: the large-scale policy bias; formalisation; knowledge politics. Corporate and state centric nature of SDGs risks entrenching large-scale bias. SDGs risk promoting an approach to formalisation that entrenches poverty and inequality. A broader knowledge of ASM governance dynamics is essential to future work. Abstract: Artisanal and small-scale mining (ASM) provides a source of livelihood for millions of mostly poor people across the globe. At the same time, however, the sector is predominantly informal and associated with a range of persistent social and environmental challenges, including chronic poverty, deforestation, land degradation, mercury pollution and river siltation. The ASM sector is connected to all the United Nations' Sustainable Development Goals (SDGs) in ways which both support and undermine their achievement. Attention, therefore, is growing on how the sector can shape, and be shaped by, the pursuit of the SDGs. This paper aims to articulate the linkages and interactions between ASM and the SDGs to inform ongoing debates about how to address the sector's social and environmental impacts. The review engages with three key, and closely related, issues that are central to determining the potential for synergies to emerge between ASM and the SDGs. These are: 1) the large-scale bias in mining policy; 2) debates around formalisation; and 3) knowledge. It is argued that the SDGs, their 169 targets and 232 indicators, and the state and corporate driven processes behind their development serve to exacerbate the large-scale bias; promote an approach to formalisation that risks marginalising the poorest and entrenching inequality, and; privilege techno-scientific knowledge at the expense of studies which examine the governance systems that actually dictate who, where, how and why people engage with ASM, knowledge that is essential for effective policy design. The review concludes that the prospects for the SDGs contributing positively to efforts to address environmental and social issues in ASM are poor. Worryingly, similar arguments apply across a range of important sectors, such as forestry and agriculture, where informality and poverty are also widespread. Raising the prospects for the SDGs requires focussing less on measuring whether or not particular indicators are met but rather on understanding what such goal-setting governance systems actually do with respect to the lives of their intended beneficiaries and the environments they inhabit. Such an understanding can inform strategies to resist the more pernicious effects of ostensibly unobjectionable global sustainability agendas.